Doing R&D or not (in a crisis), that is the question... - Michele Cincera; Claudio Cozza; Alexander Tübke; Peter Voigt (European Commission, Joint Research Centre (JRC), 2010)
This study investigates how corporate R&D evolves in the light of the contemporary economic crisis. We investigate what empirical evidence from past downturns suggests, discuss the relevant literature and perform an empirical analysis of recent business survey data (collected during 2009). We question whether companies tend to spend more or less on R&D and innovation activities during periods of recession and analyse empirically what general patterns can be distinguished in this regard, given the particular circumstances of the most recent crisis. Our findings suggest that company behaviour varies: some companies have reduced their innovation activities significantly, while others maintained them and a third group even increased their activities to reap the benefits in the expected upswing afterwards. Overall, we observe a deceleration of R&D and innovation activities in the light of the crisis, but the trend figures remain positive. Driven by the companies that reinforce their R&D and innovation efforts to thrive through the downturn and thus seek to gather the benefits in the upswing to come, the R&D and innovation landscape is likely to look different in the aftermath of the crisis. These changes will inevitably affect policy intervention in the field of innovation and are a unique chance for the reorientation of policy measures. More profoundly, they could be at the roots of a new paradigm, departing from a transition from an industrial to a knowledge-based society.
Keywords: F01; G01; O33; 330; Corporate R&D investments; innovation activities; company strategy; economic crisis; R&D globalization